Physical Characterization of Banana (Musa Paradisiaca) Peel Derived Bioplastic - Huzaisham, Nur Athirah; Marsi, Noraini; Mamat, Hasri (TRANSTELLAR, 2020)
It is challenging to Organic waste management is regarded a crucial strategy for achieving resource conservation and maintaining environmental quality. Due to their broad applications in food packaging and biomedical fields, bioplastics have drawn growing interest in recent years. These environmentally friendly polymers are gradually reducing and replacing the use of synthetic polymers based on petroleum due to their safety, low cost of production and biodegradability. This study discussed the utilization of banana (Musa Paradisiaca) peel incorporated into bioplastic. The use of banana peel (BP) in this study is mainly to replace the synthetic materials used in the conventional plastic. The preparation of samples involved several stages where banana peels were isolated from the fruits, cleaned, oven-dried at 70℃ and grinded into the range diameter of 0.23 ± 0.02 mm particle sizes. Dried ground banana peels were then extracted by maceration method and were incorporated into thermoplastic starch (TPS) with eight different concentration of BP which are 5 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, 30 wt.%, 35 wt.% and 40 wt.%. This paper highlights the recent findings attributed to the properties of the bioplastics where FTIR analysis, SEM analysis, density and porosity tests have been carried out to evaluate their physical characteristics.manage the organic fraction of municipal solid waste (OFMSW) because it is putrescible. OFMSW is dominated by food waste, and food waste is easily degradable and causes unpleasant odor at the landfill. Anaerobic digestion was preferable for food waste stabilization. However, the methane production of food waste was low. This research aims to analyze the methane yield and its kinetics from the digestion of thermally treated food waste. In preparing the thermally treated food waste, the water bath at 50°C was used and operated for two hours. The biochemical methane potential (BMP) was conducted in a batch reactor. The reactor was operated at a mesophilic temperature at inoculum to substrate ratio of 2.0. The results showed that the ultimate methane yield of thermally treated food waste increased with 630 mL CH4/g VS higher than untreated food waste. The thermal pre-treatment improved the methane production rate with an increment of 9.8%. Besides, kinetic parameters observed from Modified Gompertz modeling were found lesser than laboratory observation. Despite that, thermal pre-treatment at 50°C significantly improved the digestion of food waste.